Analisis Perbandingan Penetration Testing Tool Untuk Aplikasi Web - Bhaskara Vito Tarigan; Ari Kusyanti; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Penetration testing is a series of activities undertaken to identify and exploit security vulnerabilities. This helps confirm the effectiveness or ineffectiveness of security measures that have been implemented. This paper discusses the methodology in conducting penetration tests with a third tool penetration test is w3af, wapiti, and arachni. Penetration testing methodology includes three phases: test preparation, test and analysis test. Pilot phase involves the following steps: vulnerability analysis, information collection and analysis tool. This paper portrait is more to mengananlisa comparison tool that determines the penetration test and find out attacks anywhere that can be detected from the three tools that have been tested on existing vulnerabilities in web applications.